Cost effectiveness of adjuvant therapy for hepatocellular carcinoma during the waiting list for liver transplantation. Issue 1 (1st January 2002) - Llovet, J M; Mas, X; Aponte, J J; Fuster, J; Navasa, M; Christensen, E; Rodés, J; Bruix, J
Abstract : Background: Survival after liver transplantation for early hepatocellular carcinoma (HCC) is worsened by the increasing dropout rate while waiting for a donor. Aims: To assess the cost effectiveness of adjuvant therapy while waiting for liver transplantation in HCC patients. Method: Using a Markov model, a hypothetical cohort of cirrhotic patients with early HCC was considered for: (1) adjuvant treatment—resection was limited to Child-Pugh's A patients with single tumours, and percutaneous treatment was considered for Child-Pugh's A and B patients with single tumours unsuitable for resection or with up to three nodules < 3 cm; and (2) standard management. Length of waiting time ranged from six to 24 months. Results: Surgical resection increased the transplantation rate (>10%) and provided gains in life expectancy of 4.8–6.1 months with an acceptable cost (40 000/ year of life gained) for waiting lists ≥1 year whereas it was not cost effective (74 000/life of year gained) for shorter waiting times or high dropout rate scenarios. Percutaneous treatment increased life expectancy by 5.2–6.7 months with a marginal cost of approximately 20 000/year of life gained in all cases, remaining cost effective for all waiting times. Conclusions: Adjuvant therapies for HCC while waiting for liver transplantation provide moderate gains in life expectancy and are cost effective for waiting lists of one year or more. For shorter waiting times, only percutaneous treatment confers a relevant survival advantage.